Advertising Attitudes in West Germany and the U.S.: An Analysis over Age and Time - Anderson, Ronald D.; Engledow, Jack L; Becker, Helmut (Journal of International Business Studies, 1978)
Results of a cross-cultural, repeated measures study of advertising attitudes among subscribers toward product test magazines are presented. The subscribers, seen as an important group of purchasers and trend setters, are found to have less favorable attitudes to all aspects of advertising studied in 1976 than in 1970, both in the U.S and West Germany. Differences in attitudes among age groups are much more clearly structured in 1976, with younger subscribers showing consistently lower attitudes. Differences are found between countries, particularly in varied views of economic and social dimensions. Implications are discussed and future research suggested.